Study on Composition of Zoobenthos in Coastal Areas, Thai Binh Province - Nam, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
The zoobenthos samples were collected in 30 collecting sections from 02 nd to 13 th June and from 02 nd to 13 th October 2014. Investigation of species compositon of zoobenthos in coastal areas, Thai Binh province was identified 72 species belonging to 56 genera of 33 families, 14 orders, 4 classes (Gastropoda, Bivalvia, Crustacea, Polychaeta), 3 phyla (Mollusca, Arthropoda, Annelida). In particular, Mollusca was by far the most popular with 46 species, accounting for roughly 63.8%, compared to the figure of Arthropoda was 23 species, occupying approximately 31.9%, Annelida was 3 species, occupying approximately 4.3%. The density of zoobenthos at the sampling sites averaged from 17 to 420 individuals/m 2 . The Shannon-Weiner (H') diversity index at the study sites averaged from 2.13 to 3.63.